(untitled) (CIPEEX, 2022)
AGING IS RESPONSIBLE FOR PHYSICAL AND PSYCHOLOGICAL CHANGES IN THE BODY, GENERATING FEELINGS OF INCAPACITY, WORTHLESSNESS AND SELF-DEVALUATION, WHICH CAN FAVOR THE DEVELOPMENT OF DEPRESSIVE CONDITIONS. THESE EPISODES ARE MARKED BY LOWERING OF MOOD, ABULIA, LOSS OF VOLITION, ANHEDONIA, FEELINGS OF GUILT, INCREASED OR DECREASED APPETITE, INSOMNIA OR HYPERSOMNIA, AND ATTENTION DEFICITS. WITHIN THIS CONTEXT, PHYSICAL ACTIVITIES HAVE PLAYED A ROLE IN HEALTHY AGING, ESPECIALLY WATER AEROBICS, WHICH INCREASES QUALITY OF LIFE, IMPROVES PHYSICAL FUNCTIONALITY AND PROVIDES FEELINGS OF WELL-BEING, FIGHTING DEPRESSIVE SYMPTOMS. THEREFORE, THE PRESENT STUDY AIMS TO IDENTIFY THE PRESENCE OF DEPRESSION IN THE ELDERLY ENROLLED IN A WATER AEROBICS PROGRAM, ANALYZING THE INFLUENCE OF PHYSICAL EXERCISE ON THE MENTAL HEALTH OF THIS POPULATION. TO CARRY OUT THE WORK, THE ENTIRE ELDERLY POPULATION ENROLLED IN HYDROGYMNASTICS PROJECT OF THE UNIVERSIDADE ABERTA A PESSOA IDOSA (UNIAPI) OF THE EVANGELICAL UNIVERSITY OF GOIS - UNIEVANGLICA WAS EVALUATED. ALL ELDERLY MEMBERS OF THIS SPORT WERE INCLUDED AND THOSE WHO WERE ABSENT IN AUGUST OR WHO REFUSED TO PARTICIPATE IN THE RESEARCH WERE EXCLUDED FROM THE SAMPLE. THE MAIN RISKS OF THE WORK CONSISTED OF THE EMBARRASSMENT OF THE PARTICIPANTS, WHO HAD COMPLETE PRIVACY TO CARRY OUT THE QUESTIONNAIRES APPLIED. THE TOOL USED FOR EVALUATION WAS THE HAD SCALE - ASSESSMENT OF THE LEVEL OF ANXIETY AND DEPRESSION, APPLIED IN EARLY AUGUST 2022 AND AT THE END OF THE SAME MONTH. THEN, THE COLLECTED DATA WERE STORED IN A SPREADSHEET AND COMPARED WITH EACH OTHER, SEEKING TO ANALYZE THE PROFILES OF CHANGES FOUND OVER THE PERIOD STUDIED. THUS, EACH RESULT OF THE HAD SCALE INDICATED UNLIKELY (SCORES FROM 0 TO 7), POSSIBLE (SCORES FROM 8 TO 11) AND PROBABLE (SCORES FROM 12 TO 21) CASES OF DEPRESSION. THUS, IT WAS OBSERVED THAT 56.5% OF THE PARTICIPANTS WERE UNLIKELY CASES, 34.8% POSSIBLE CASES AND 8.7% PROBABLE CASES. AFTER 30 DAYS, THE NUMBER OF UNLIKELY CASES INCREASED TO 69.5%, WHILE THE POSSIBLE AND PROBABLE CASES DECREASED TO 26.1% AND 4.4%, RESPECTIVELY. FROM THESE VALUES, AN IMPROVEMENT IN DEPRESSION RATES WAS IDENTIFIED AFTER THE PRACTICE OF WATER AEROBICS REGULARLY, THUS, IT WAS FOUND THAT THIS SPORT MODALITY IS BENEFICIAL FOR THE CONTROL OF DEPRESSIVE DISORDERS. KEYWORDS: DEPRESSION. ELDERLY. PHYSICAL ACTIVITY. QUALITY OF LIFE OF THE ELDERLY.